(untitled) (Research, Society and Development, 2023)
Introduction: Pulmonary arterial hypertension (PAH) is hemodynamically characterized by a mean pulmonary artery pressure (mPAP) >20 mmHg at rest. Patients with Systemic Sclerosis (SS) can be affected by PAH and evolve with a reserved prognosis. The gold standard for diagnosis is right heart catheterization, but non-invasive methods allow anatomical and functional monitoring to assess severity and treatment. The Cardiopulmonary Exercise Test (CPET) assesses the aerobic condition, the possible mechanism responsible for reduced exercise capacity and prognostic markers, and its role in patients with SSc and PAH is recognized. Objective: the study aims to use the cardiopulmonary exercise test in the differential diagnosis of dyspnea in a patient with primary pulmonary hypertension. Methodology: This is a case report associated with a literature review. Conclusion: In the clinical case addressed, the importance of CPET in the differential diagnosis of dyspnea and in the evaluation of prognostic markers is evident, helping in the therapeutic decision, in order to provide better quality of life and survival of patients.